The National Liberation Army, Peacebuilding and its Sustainability in Colombia - Onur Ağkaya (Güvenlik Stratejileri Dergisi)
The Colombian civil war has been going on for 60 years. Currently, one of the key warring factions is the Ejército de Liberación Nacional (ELN - National Liberation Army), recognized as the oldest active guerrilla organization in Latin America. The ELN is a formation that differs from other guerrilla organizations in Colombia. The study primarily seeks to answer the research question of “Will the ELN’s differences from other organizations affect the peace processes in Colombia?”. The study examines the ELN’s historical development, structure, and action repertoire since its emergence, presenting an analysis of peacebuilding in Colombia and its future. Following the research question and adopting a historical-sociological interpretative perspective as methodology, the study aims to contribute to conflict resolution and peace studies in Türkiye by examining the examples of the ELN and Colombia. This study contends that the ELN has a distinctive structure; accordingly, negotiations with this organization should be handled with a more comprehensive agenda and approach than those of other guerrilla organizations in Colombia. Lastly, the study argues that even if the ELN agrees to disarmament, peace in Colombia is far from achievable and sustainable, at least in the short term.